EXAMINING OF E-MARKETING, INFORMATION SYSTEM AND UNIVERSITY BRAND IMAGE ON STUDENT DECISION - Rizan Machmud; David P.E. Saerang; Agus Supandi; Rudy S Wenas (Journal of International Conference Proceedings (JICP), 2018)
The large number of higher education in Indonesia, forced higher education especially universty to improve its competitiveness to maintain its students as consumers. One of the history of education in Indonesia is the issuance of Presidential Decree of the Republic of Indonesia Number 93 year 1999 which "stone" teacher institute (IKIP) wider mandate to University which called as LPTK university. The born of LPTK University make the number of competition between universities were increased. However, LPTK universities are perceived lose on competition with universities instead of former IKIP. To maintain from competition LPTK university is required to improve their image. This literature study focuses on how e-marketing factor utilization through the use of university website is expected to support LPTK university image. In addition, the information system developed by LPTK universities should be able to build convenience for their respective students. It is assumed through a good information system the image of the university also awakened. In turn e-marketing strategy and building a good information system will help improve the university brand image and inspire the interest of students to choose and continue their study at LPTK universities in Indonesia. Keyword : university, LPTK, university brand image, e-marketing, information system